Surveillance for ototoxicity in platinum-based chemotherapy using mobile health audiometry with extended high frequencies. Issue 1 (25th May 2022) - Ehlert, K; Heinze, B; Graham, M A; Swanepoel, D
Abstract: Objective: This study investigated mobile health enabled surveillance in ototoxicity. Method: This was a longitudinal study of 32 participants receiving chemotherapy. Baseline and exit audiograms that included conventional and extended high frequency audiometry were recorded within the patient's treatment venue using a validated mobile health audiometer. Results: Average hearing thresholds at baseline were within the normal range (81.2 per cent left; 93.8 per cent right), reducing at exit testing (71.9 per cent left; 78.1 per cent right). Half of participants presented with a threshold shift according to ototoxicity monitoring criteria. The frequencies affected the most were between 4000 and 16 000 Hz, with left ears significantly more affected than right ears. Noise levels exceeded the maximum permissible ambient noise levels in up to 43.8 per cent of low frequencies (250–1000 Hz). Conclusion: Mobile health supported audiometry proved to be an efficacious tool for ototoxicity monitoring at the treatment venue. Changes in hearing ability over time could be tracked, improving surveillance in patients with full treatment schedules.